Incidence of upper respiratory tract infections with biological therapies in moderate to severe atopic dermatitis: a systematic review and meta-analysis - Rose Alraddadi; Rose Alraddadi; Mulham Kalantan; Mulham Kalantan; Yara Aljefri; Yara Aljefri; Hadeel Maaddawi; Abdulrahman Alsamadani; Abdulrahman Alsamadani; Athoub Kadasa; Athoub Kadasa; Abdulrahman Softah; et al. (Frontiers in Medicine)
IntroductionAtopic dermatitis (AD) is a chronic inflammatory skin condition affecting 5%−20% of children and 2%−10% of adults worldwide. Treatment for moderate-to-severe AD includes biologics like dupilumab, tralokinumab, lebrikizumab, and JAK inhibitors (abrocitinib, upadacitinib). However, upper respiratory tract infections (URTIs) are commonly reported adverse events for these therapies. This meta-analysis aims to estimate the pooled incidence of URTIs associated with these treatments compared to topicals.MethodsA systematic search was conducted across PubMed, MEDLINE, DOAJ, and ClinicalTrials.gov for randomized controlled trials (RCTs) involving AD patients treated with dupilumab, tralokinumab, lebrikizumab, abrocitinib, or upadacitinib, excluding studies of patients treated with topicals, Studies on other dermatitis types and biologics. Data on URTI events, sample sizes, and incidence were extracted. Study quality was assessed using the Cochrane Risk of Bias Tool (RoB 2). A random-effects meta-analysis was conducted using the Netmeta package in R, calculating odds ratios (ORs) with 95% confidence intervals (CIs).ResultsFrom 413 retrieved records, 21 studies met the inclusion criteria. URTI incidence of the treatment group in the included studies ranged from 0.35% to 41.5%, while control groups showed rates between 0% and 40%. Across all studies, URTI incidence was 9.70% in intervention groups and 8.03% in placebo groups (MH OR = 1.18, 95% CI: 0.98–1.42). Heterogeneity was low (I2 = 20.14%), with no evidence of publication bias (p = 0.83). There were no significant subgroup differences between patients taking different biological therapies (Q = 3.90, p = 0.42).ConclusionWhile URTIs are common adverse events for AD therapies, their incidence in intervention groups is similar to control, suggesting no significant increase in risk. These findings provide critical insights for clinicians in balancing efficacy and safety when selecting therapies for AD patients. Further research should explore patient-specific risk factors for URTIs.Systematic review registrationProspero registration code: [392093]. PROSPERO, Centre for Reviews and Dissemination: CRD42023392093.